Predictive factors for stem cell mobilization failure in multiple myeloma patients: A single center experience. (February 2020) - Goker, Hakan; Ciftciler, Rafiye; Demiroglu, Haluk; Turgut, Mehmet; Sayınalp, Nilgun; Haznedaroglu, I.C.; Okay, Mufide; Tekin, Fatma; Buyukasık, Yahya
Abstract: Background and aim: High-dose chemotherapy followed by autologous stem cell transplantation (ASCT) has been considered the standard of treatment care for patients with multiple myeloma (MM). Insufficient mobilization and harvest of peripheral stem cells can be a major obstacle for performing ASCT. This is resulting in a lacking opportunity of cure in patients with MM. The aim of this study was to evaluate the factors which influence mobilization failure in patients with MM. Materials and methods: This study has been performed in a retrospective manner. Two hundred and thirty-four patients with diagnosed MM who underwent stem cell mobilization after induction chemotherapy at Hacettepe University Hospital between the years of 2003 and 2018 were evaluated. Results: A total of 234 patients were included in this study. The median age was 54 (32–76) years at the time of diagnosis. In 209 of 234 patients (89.3%) first mobilization trial was successful. At univariate analysis, among parameters identifiable before mobilization, male gender (p = 0.03), number of chemotherapy cycle before stem cell mobilization (p < 0.001), second ASCT (p < 0.001) and immunomodulatory treatment before stem cell mobilization (p < 0.001) predicted mobilization failure. At multivariate analysis, number of chemotherapy cycle before stem cell mobilization (p = 0.03), second ASCT (p < 0.001) and immunomodulatory treatment before stem cell mobilization (p = 0.02) retained independent predictive power. Conclusion: Detectable different clinical characteristics of MM patients before initiating mobilization may be predictors of poor mobilization. Therefore, the mobilization protocol should be evaluated on a patient basis. Minimization of exposure to chemotheraputic agents in MM patients, especially immunomodulatory agents, may increase CD34+ cell harvest yields.